Different mazhab views on family issues today - Mohd Aznan, Anees Mysarah; Yaakob, Fathiah; Mazlan, Nur Adleen Maisarah; Mat Nazin, Nur Hanan; Wan Sakiman, Wan Dalila Akmal (2025)
Among the most important topics covered by Islamic law are family matters like marriage, divorce, child custody, and inheritance. Muslim societies’ moral and social structures are greatly influenced by these issues. Within Islam, the four main schools of Sunni thought which is Hanafi, Maliki, Shafie, Hanbali represent a rich legal legacy. Different legal approaches, principles (usul al-fiqh), and interpretations based on the Quran, Hadith, consensus (ijma’), and reasoning (qiyas) are applied by each mazhab. Due to historical, regional, factor, these variances result in varying decisions on comparable family matters (Hassan, 2016). When it comes to practical issues like inheritance, divorce proceeding, or the guardianship function in marriage contracts, the differences mazhab viewpoints become very important. For example, the Shafie school believes that the guardian’s approval is necessary, whereas the Hanafi school permits a woman to enter her own marriage without guardian. Regarding inheritance, (Nizaita Omar & Zulkifly Muda, 2017) describe how shifting one’s beliefs might lead to various heirs receiving varying shares of the estate. This is especially important in nations with pluralistic legal systems, where Muslims may consult different mazhab for rulings on certain legal or private matters. Their research demonstrates how crucial jurisprudential knowledge is to ensuring fairness and justice in family affairs. The incorporation of many mazhab viewpoints into the legal system in modern Muslim cultures such as Malaysia demonstrates the fluidity of Islamic law. Even while the Shafie school is the most widely used legal reference, other schools, including Hanafi may occasionally be applied to meet unique situations, especially in complex family matters. (Mohd, 2019) examines how the Islamic Family Law (Federal Territories) Act 1984 incorporates Hanafi decisions, exposing a purposeful legal approach to make Islamic law more inclusive and workable. In addition to demonstrating the Shariah’s adaptability, this flexible and context-sensitive methodology guarantees its ongoing relevance in a world that is changing. Scholars and practitioners can promote more compassionate and comprehensive resolutions to family conflicts by contrasting various mazhab interpretations.